Corporate Restructuring of a Conglomerate: A Case of Arvind Limited - Rohit Singh, Vivek Divekar (International Journal of Modern Agriculture, 2020)
Arvind Limited, a conglomerate, exercised demerger as its preferred tool of corporate restructuring twice, first in the year 2015 when it demerged its real estate undertaking and second in the year 2018 when it demerged its branded apparel and two of its engineering undertakings. This is a company that carried forward its experience of restructuring through demerger and chose the same option again to restructure its business in just a span of three years. ‘Event study’ technique is used here to examine effect of announcement of demerger on the wealth of the shareholders and market model has been used in this study using log returns. Results of parametric and non-parametric tests have been compared with each other to check their consistency. Traditional and modern empirical tools have been used to measure the performance of Arvind Limited and compare them through the timeline. A glimpse of the performance of the companies carved out of the parent company, is also studied here to have a broader perspective of the impact of this corporate strategy. This form of restructuring is unique and its usage is on the rise with every passing year all around the world.